The International Development (Official Development Assistance Target) Act 2015: Legislative Spending Targets, Poverty Alleviation and Aid Scrutiny. Issue 4 (1st July 2016) - Manji, Ambreena
Abstract : With the enactment of the International Development (Official Development Assistance Target) Act 2015, the United Kingdom has enshrined an aid target in law. It is now under a legal duty to spend 0.7% of Gross National Income (GNI) each year on aid. This article assesses the implications of enshrining a spending target for development assistance in law. It argues that commentators have focused their analyses too narrowly on the legal target and that it is in fact the mechanisms for scrutinising development assistance contained in section 5 of the new Act that will be important in future. This is because judicial scrutiny of aid spending is a remote possibility as a result of the International Development Act 2002. The article provides an analysis of the new legislation in the context of the UK's now detailed legislative framework for international development aid and concludes that this framework is far from satisfactory.